Xanthogranuloma of nose in an adult: an uncommon presentation - Palo, Seetu; Barsagade, Ashwinkumar K.; Sikdar, Neha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Xanthogranuloma is a relatively rare histiocytic cutaneous disorder that typically affects the pediatric age group. Its occurrence in adulthood is still rarer with only a handful of cases on the record. The present case report describes a case of adult-onset xanthogranuloma in a 49 years old lady who presented to the otorhinolaryngology clinic with a 6 months history of a nodule on the left side of the columella. There was no history of associated pain or bleeding from the site. Local examination revealed a 0.6×0.6 cm, non-tender, soft-to-firm, pinkish dome-shaped lesion with rounded edges. No similar lesions were found elsewhere. Excisional biopsy of the lesion was performed and microscopy showed a dermal lesion comprising of sheets of histiocytes admixed with lymphoplasmacytic infiltrate, touton giant cells and few spindle cells. A diagnosis of xanthogranuloma was rendered. A number of lympho-histiocytic lesions comes in the differential diagnosis of xanthogranuloma and hence it is important to be aware of such unusual presentations in order to make correct histological diagnosis.